Tanggapan Pelanggan terhadap Pelayanan Hotel Oasis Banda Aceh - Amrusi Amrusi; Nora Afriyanti (Universitas Serambi Mekkah, 2018)
This study aims to find out customer expectations for the services of Banda Aceh Hotel Oasis. The object in this study is the quality of service, and the subject is the Oasis Banda Aceh hotel. Sampling is done using the accidental sampling method. Samples of 30 respondents who were using the Oasis Hotel Banda Aceh lodging service at least 2 times. Data was obtained using questionnaires, and processed on average. The results of research for service reliability variables obtained an average response of 3.50 which is classified as good. For responsive service variables, the respondent's response is 3.63 which is relatively good. For the belief service variable, the respondent's response is 3.65 which is also relatively good. For the empathy variable, the value is 3.23 which is categorized as sufficient or adequate. The average tangible variable is assessed by consumers as 3.44, which means that the service in the tangible dimension given by the Banda Aceh Oasis Hotel is relatively standard or sufficient. Overall the quality of service at the Oasis Hotel Banda Aceh for the five dimensions is categorized as good with an average value of 3.50. To foster a sense of trust in customers, it is recommended that employees should always be given training so that they are capable and skilled in carrying out their duties.